Answer:
The solution of above equation is x = 3.
Step-by-step explanation:
We have given a quadratic equation.
2x-3 = x²/3
We have to find the value of x.
Multiplying both sides of given equation by 3, we have
3(2x-3) = 3(x²/3)
6x-9 = x²
Simplifying above equation,we have
x²-6x+9 = 0
Splitting the middle term of above equation, we have
x²-3x-3x+9 = 0
Making groups , we have
x(x-3)-3(x-3) = 0
Taking (x-3) as common, we have
(x-3)(x-3) = 0
Applying Zero-Product Property to above equation, we have
x-3 = 0 or x-3 = 0
x = 3 or x = 3
Hence,The solution of above equation is x = 3.